Pilotprojekt Gropiusstadt : Jahrbuch 2006. (Berlin : Kulturnetzwerk Neukölln Berlin, 2006)
Becker, Isabel ; Bölter, Frank ; Brand, Martin ; Brellochs, Mari ; Bunte, Andreas ; Busch, Astrid ; Eisenlohr, Klaus ; Erlenwein, Annette ; Friederike & Uwe ; Glanz, Katrin ; Göttke, Florian ; Grundheber, Cap ; Harskamp, Nicoline ; Hegardt, Björn ; Henn, Vanessa ; Wille, Barbara ; Désert, Jean-Ulrick ; Henrich, Sylvia ; Horst, Philip ; Huseby, Benjamin ; Jambon, Patrick ; Karcheter, Judith ; Kurr, Stephan ; Lockemann, Ingeborg ; McGeorge, Eline ; Micheel, Stefan ; Paas, Jürgen ; Schlegelmilch, Karola ; Schömig, Claudia ; ststs ; Templin, Andreas ; Weis, Albert ; Witzmann, Andrea ; Zeitler, Johann
zie kast losse tijdschriften
Duits
boek